Outcome of vitrified-warmed blastocyst transfer performed on days 5–7 after urine LH detection. Issue 4 (April 2022) - Gavrić Lovrec, Vida; Kozar, Nejc; Reljič, Milan
Abstract: Research question: What is the clinical importance of vitrified-warmed blastocyst transfer timing if performed on days 5, 6 and 7 after detecting the LH surge using urine tests? Design: Between 2013 and 2019, 2080 vitrified-warmed blastocyst transfers in a true natural cycle were performed and later analysed at the Department of Reproductive Medicine, University Medical Centre Maribor, Slovenia. Urine LH tests were performed twice daily to monitor the onset of the LH surge. Vitrified-warmed blastocyst transfer (frozen embryo transfer [FET]) was performed on day 5 (group 1), 6 (group 2) or 7 (group 3) after the LH surge in 18%, 77% and 4% of cycles, respectively. The patient and cycle characteristics among the groups were compared using the Cochran–Mantel–Haenszel test and respective generalized linear mixed models. Propensity score matching was used to adjust for potential differences among the groups. Results: There were no statistically significant differences between groups 1, 2 and 3 in the cycle and patient characteristics, clinical pregnancy rate (38% versus 39% versus 31%), implantation rate (34% versus 36% versus 31%), miscarriage rate (7% versus 9% versus 7%) and delivery rate (31% versus 31% versus 24%). The day of FET after the LH surge detected using a urine test was not significantly associated with live births. Conclusions: The results of the current study suggested that the vitrified-warmed blastocyst transfer could be scheduled on day 5, 6 or 7 after a positive LH urine test without having a significant impact on the clinical outcome.